2020
DOI: 10.1101/2020.05.01.072066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GCN sensitive protein translation in yeast

Abstract: MPW) ¶ These authors contributed equally to this work. AbstractLevels of protein translation by ribosomes are governed both by features of the translation machinery as well as sequence properties of the mRNAs themselves. We focus here on a striking three-nucleotide periodicity, characterized by overrepresentation of GCN codons and underrepresentation of G at the second position of codons, that is observed in Open Reading Frames (ORFs) of mRNAs. Our examination of mRNA sequences in Saccharomyces cerevisiae reve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Alternatively, increasing H-bonding to the CAR surface could make ribosome-mRNA interaction too ‘sticky’, possibly hindering the threading of the mRNA and reducing translocation efficiency. We hypothesize that both scenarios are true, depending on the strength of the mRNA–CAR interactions and translation level of the gene [ 8 ]. For low-expression genes, which tend to have low or modest GCN periodicity in their ramp, increasing mRNA–CAR interactions may promote translation, whereas for high-expression genes, which tend to have strong GCN periodicity, increased mRNA–CAR interactions may depress translation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, increasing H-bonding to the CAR surface could make ribosome-mRNA interaction too ‘sticky’, possibly hindering the threading of the mRNA and reducing translocation efficiency. We hypothesize that both scenarios are true, depending on the strength of the mRNA–CAR interactions and translation level of the gene [ 8 ]. For low-expression genes, which tend to have low or modest GCN periodicity in their ramp, increasing mRNA–CAR interactions may promote translation, whereas for high-expression genes, which tend to have strong GCN periodicity, increased mRNA–CAR interactions may depress translation.…”
Section: Discussionmentioning
confidence: 99%
“…For low-expression genes, which tend to have low or modest GCN periodicity in their ramp, increasing mRNA–CAR interactions may promote translation, whereas for high-expression genes, which tend to have strong GCN periodicity, increased mRNA–CAR interactions may depress translation. In this model [ 8 ], increased mRNA–CAR interactions under stress conditions would result in up- or down-regulation of translation, depending on a gene’s expression level and the strength of its ramp GCN periodicity. Since genes with high protein expression tend to have strong GCN periodicity in their ramp regions, translation of these genes would be depressed under stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in the Weir lab found that the ramp region, codons 3 to 7 of the open reading frame (ORF), of yeast genes has an overrepresentation of G at codon position 1 and C at position 2 coupled with an underrepresentation of G at position 2 (Figure I.6A) (Barr et al, 2020). This GCN periodicity is more pronounced in highly expressed proteins.…”
Section: Ib Gcn Periodicity May Mediate Translation Levelsmentioning
confidence: 89%
“…Mass spectrometry detected proteins showed a depression of G at position 2 of codons 4 to 7 in highly expressed proteins (Figure I.6B) (Lycette et al, 2016). Additionally, an analysis of the mRNA sequence of the ramp region, showed that the top 10% of genes had more pronounced GCN periodicity with a depression of G at position 2 (Figure I.6C) (Barr et al, 2020). Thus, GCN periodicity is most pronounced in the ramp regions of highly expressed genes.…”
Section: Ib Gcn Periodicity May Mediate Translation Levelsmentioning
confidence: 94%